Enhancing free choice masked priming via switch trials during repeated practice - Dai, Qi; Yao, Lichang; Wu, Qiong; Yu, Yiyang; Li, Wen; Yang, Jiajia; Takahashi, Satoshi; Ejima, Yoshimichi; Wu, Jinglong (Frontiers in Psychology, 2022)
The masked priming paradigm has been extensively used to investigate the indirect impacts of unconscious stimuli on conscious behaviors, and the congruency effect of priming on free choices has gained increasing attention. Free choices allow participants to voluntarily choose a response from multiple options during each trial. While repeated practice is known to increase priming effects in subliminal visual tasks, whether practice increases the priming effect of free choices in the masked priming paradigm is unclear. And it is also not clear how the proportions of free choice and forced choice trials in one block will affect the free choice masked priming effect. The present study applied repeated practice in the masked priming paradigm and found that after training, the participants were more likely to be influenced by masked primes during free choice, but this training process did not alter the visibility of masked stimuli. In addition, this study revealed that when the proportions of free choice and forced choice trials were equal during the training stage, this enhanced effect by practice was the strongest. These results indicated that practice could enhance masked stimulus processing in free-choice, and that the learning effect may mainly be derived from the early selection and integrated processing of masked stimuli.